Prevalence and Risk Factors of Erectile Dysfunction in Patient Visiting Andropause Clinic, Srinagarind Hospital, Thailand - Eamudomkarn, Nuntasiri; Khampitak, Kovit; Xothornwit, Jen; Phunikhom, Kutcharin; Kunatippapong, Nantaya; Khampitak, Tueanjit; Chatvised, Phanwadee (ศรีนครินทร์เวชสาร, 2014)
Objectives: To assess the prevalence and risk factors of erectile dysfunction (ED) in male patients visiting andropause clinic, Srinagarind hospi¬tal, Khon Kaen university, Thailand. Methods: A retrospective study was conducted in all patients who came to the clinic during 2003-2013. The data were collected from computerized medical records which ED was assessed by Modified SHIM-IIEF5 questionnaire. Results: Three hundred and sixty patients were recruited in this study. The mean age of the patients was 58.9 year-old (58.9+/-8.3 year-old) and the mean BMI was 24.2 kg/m2 (24.2+/-3.0 kg/m2). Of the 360 patients, 31.1%, 28.1%, and 17.5% had underlying disease of dyslipidemia, hypertension, and diabetes mellitus, respectively. The prevalence of benign prostatic hyperplasia, chronic kidney disease and malignancy were higher in older patients, especially in age more than 60 year-old. The prevalence of ED was 83.3%. The statistically significant risk factors for ED were diabetes mellitus (OR 4.75, 95%CI 1.44-15.69) and renal impairment (OR 1.21, 95% CI 1.15-1.26). In contrast, exercise was a protective factor for ED (OR 0.74, 95% CI 0.30-1.84). Conclusion: In Andropuase clinic, we found higher prevalence of ED than general population. The significant risk factors among these patients were diabetes mellitus and renal impairment. ED screening should be recommended in all andropause men to improve the quality of life.